The Relation between Contraception Methods and Quality of Life - Narjes Bahri; Hamid R Tohidinik; Roghayeh R Bilandi; Mona Larki; Fatemeh Hooshangi; Maliheh Soltanian (Epidemiology, Biostatistics and Public Health)
Objectives:  Assess the relationship between contraception methods and quality of life in women of reproductive age.